2014
DOI: 10.1177/0963662514536295
|View full text |Cite
|
Sign up to set email alerts
|

Audience reach of science on television in 10 European countries: An analysis of people-meter data

Abstract: Beginning with a differentiation of science programmes into five different editorial concepts, this article explores the audience reach of science on television in ten European countries with a special emphasis on young audiences aged between 14 and 29. In relation to the share of this age group in the entire population, science programmes in all countries reach a considerably smaller proportion of younger viewers. Specific preferences for science content on television do not seem to be relevant in explaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 17 publications
0
3
0
4
Order By: Relevance
“…The effectiveness of science communication through various media closely relates to the specific forms and practices of communication, but also the factors and preferences of the recipients. Prior research already showed that utilised channels, and consequentially also the effectiveness of information transition differ by individual characteristics, such as education (Chang et al 2017), gender, age (Lehmkuhl et al 2016), and religiosity (Scheufele et al 2009). Other studies illustrate that popular media not only transmit information about science, but also provide scientific education (Allgaier 2012;Szu et al 2016), narrow the knowledge gap in society (Chang et al 2017), and create various types of science perceptions and interpretations (Lörcher and Taddicken 2017).…”
Section: Science Communication -How the Public Is Informed And How Pementioning
confidence: 99%
“…The effectiveness of science communication through various media closely relates to the specific forms and practices of communication, but also the factors and preferences of the recipients. Prior research already showed that utilised channels, and consequentially also the effectiveness of information transition differ by individual characteristics, such as education (Chang et al 2017), gender, age (Lehmkuhl et al 2016), and religiosity (Scheufele et al 2009). Other studies illustrate that popular media not only transmit information about science, but also provide scientific education (Allgaier 2012;Szu et al 2016), narrow the knowledge gap in society (Chang et al 2017), and create various types of science perceptions and interpretations (Lörcher and Taddicken 2017).…”
Section: Science Communication -How the Public Is Informed And How Pementioning
confidence: 99%
“…Saber Vivir es heredero natural de Más vale prevenir, dirigido y presentado por Ramón Sánchez Ocaña, un espacio que obtuvo mucho éxito y marcó un precedente en los espacios matutinos (Moreno Castro, 2004: 130). El programa se clasifica según la tipología de Lehmkuhl et al (2012Lehmkuhl et al ( y 2016 como Advice Programmes o programas de consejos, en los que la inversión de tiempo y esfuerzo en los contenidos científicos no es poca.…”
Section: Corpus Y Metodologíaunclassified
“…Este programa se situaría en la tipología de Lehmkuhl et al (2012Lehmkuhl et al ( y 2016 en la categoría de Edutainment Programmes, pues aunque no sea similar a los ejemplos que los autores ofrecen, entendemos la docuficción como una forma de divulgar aspectos reales a través de formatos mejor acogidos por el público.…”
Section: Centro Médicounclassified
See 2 more Smart Citations